Optimization of risk management in red chili agribusiness through factoring financing using a system dynamics approach in Aceh Tengah Regency - Hakim, Lukman; Arida, Agustina (AGROMIX, 2025)
Introduction: The production and marketing of red chili in Aceh Tengah Regency face significant risks, particularly financial constraints that limit liquidity and undermine the sustainability of farming systems. Prolonged receivable structures remain a major challenge, restricting farmers’ working capital and reducing supply chain efficiency. This study aims to optimize financial risk management in red chili agribusiness through the application of factoring as an alternative financing scheme, using a system dynamics approach. Methods: A system dynamics approach was employed to analyze the role of factoring as an alternative financing mechanism in red chili agribusiness. The research was conducted in the main chili production centers of Aceh Tengah Regency using a mixed-method design that combined literature review, field observations, and in-depth interviews with farmers, cooperatives, financial institutions, and policymakers. Primary and secondary data were integrated into a dynamic simulation model using Vensim software to assess the impact of factoring on cash flow, liquidity, and system sustainability. Results: The simulation results demonstrate that factoring effectively accelerates cash inflows, thereby strengthening farmers’ liquidity compared to delayed payments of up to 30 days under conventional arrangements. Enhanced liquidity enables farmers to finance production inputs, labor, and crop maintenance more efficiently, while cooperatives benefit from more stable cash flows to ensure timely payments to members. Additional advantages include improved sales administration and collection systems, reduced credit default risk, and greater competitiveness without collateral requirements. Conclusion: Factoring is proven to be a viable financing strategy that enhances the resilience and sustainability of red chili farming systems by improving liquidity and supply chain efficiency. Policy implications include the need to establish supportive regulations, promote transparency in factoring costs, and encourage cooperative-based financing schemes to facilitate wider adoption among smallholder farmers.